Skin damage induced by enhanced protective measures in frontline doctors during Covid-19 pandemic: A web-based descriptive study - Mahimanjan Saha; Indrashis Podder; Anupam Das (Wolters Kluwer Medknow Publications, 2021)
Background: Frontline doctors engaged in COVID-19 duties have to adopt enhanced protective measures to minimize their risk of exposure. However, these measures may lead to several skin problems, thereby affecting their performance. Objectives: To analyze skin changes induced by enhanced protective measures and explore possible risk factors. Materials and Methods: A web-based descriptive study was conducted among 212 frontline COVID-19 doctors. Data were collected regarding their demography, duty, use of enhanced protective measures including prophylactic hydroxychloroquine, recent skin changes with affected sites, and possible risk factors. Results: Skin changes were reported by 41.5% of respondents (mean age 34.8 ± 5.6 years) across 210 sites. Hands were involved most commonly in 77.3% of doctors, followed by nasal bridge, cheeks, and retroauricular area. Dryness (84.1%) and skin peeling (79.5%) were the commonest clinical features. Regression model showed prolonged PPE wear (>6 h) adjusted odd's ratio (AOR) 2.9, P = 0.005], heavy sweating [AOR 12.8, P = 0.001] and frequent hand hygiene (>10 times/day) [AOR 3.1, P = 0.0006] to be significant risk factors. Hydroxychloroquine prophylaxis was deemed safe as treatment-emergent adverse events were uncommon (17.4%). Conclusion: Frontline doctors have an increased risk of developing skin damage due to enhanced protective measures. Appropriate steps should be taken to address the risk factors and minimize skin damage. Persistent cases mandate dermatology referral for optimum management.